Characterizing the Virome of Apple Orchards Affected by Rapid Decline in the Okanagan and Similkameen Valleys of British Columbia (Canada) - Huogen Xiao; Wenjia Hao; Gavin Storoschuk; Jesse L. MacDonald; Hélène Sanfaçon (Pathogens, 2022)
Rapid apple decline disease (RAD) has been affecting orchards in the USA and Canada. Although the primary cause for RAD remains unknown, viruses may contribute to the incidence or severity of the disease. We examined the diversity and prevalence of viruses in orchards affected by RAD in the Okanagan and Similkameen Valleys (British Columbia, Canada). Next-generation sequencing identified 20 previously described plant viruses and one viroid, as well as a new ilarvirus, which we named apple ilarvirus 2 (AIV2). AIV2 was related to subgroup 2 ilarviruses (42–71% nucleotide sequence identity). RT-PCR assays of 148 individual leaf samples revealed frequent mixed infections, with up to eight viruses or viroid detected in a single tree. AIV2 was the most prevalent, detected in 64% of the samples. Other prevalent viruses included three ubiquitous viruses from the family Betaflexiviridae and citrus concave gum-associated virus. Apple rubbery wood virus 1 and 2 and apple luteovirus 1 were also readily detected. The thirteen most prevalent viruses/viroid were detected not only in trees displaying typical RAD symptoms, but also in asymptomatic trees. When compared with reports from orchards affected by RAD in Pennsylvania, New York State, and Washington State, regional differences in relative virus prevalence were noted.